Game Virtual Reality Sorgum Untuk Ketahanan Pangan - Delta Ardy Prima; Mikhael Ming Khosasih (LPPM UBHINUS MALANG, 2025)
Sorghum is a vital staple food crop widely consumed in Asia and Africa, ranking among the top five food crops globally after wheat, corn, rice, and barley. It is rich in carbohydrates and low in sugar, making it a suitable dietary option for individuals with diabetes. Sorghum can be cultivated on marginal or unproductive land; however, improper cultivation techniques may lead to sub-optimal yields or even crop failure. Survey findings indicate that public awareness and knowledge about sorghum cultivation in Indonesia remain limited, contributing to difficulties in effective planting and crop management. To address this issue, a simulation game utilizing virtual reality (VR) technology was developed to provide an interactive and immersive learning experience for sorghum cultivation. The Unity game engine was employed in the development process, incorporating freely available assets from various sources. The application was validated through expert interviews and user testing within the community. Post-testing results demonstrated a 31% increase in user knowledge regarding sorghum cultivation. These findings suggest that the VR-based game effectively enhances public understanding of the procedures involved in planting and maintaining sorghum crops.